Propuesta para el sistema de tratamiento de agua residual del proceso de nitruración en la empresa Aluica S.A.S. (2018)
In this work, a proposal is made for the treatment and recirculation of the residual water from the nitriding process of the company Aluica SAS, in order to promote the formal reactivation of the process of being guarded by the control control entities due to the generation of discharges of uncontrolled non-domestic waters. Initially, the diagnosis of the nitriding process and the relationship with the wastewater emitted was made, this requires a historical analysis of the process, the technical evaluation of the process and the physical and chemical characteristics of the wastewater. As a result, the need to develop the treatment of these waters has been verified to obtain a strongly alkaline pH of 10.62 and a temperature of 40.4°C, values outside the permissible limits issued in Resolution 0631 of 2015, in addition of an ammonia concentration of up to 1333 mg /l.